Pembelajaran Bahasa Arab dengan Pendekatan Analisis Morfologi - Natsir, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2017)
Arabic is a series of operations and processes train students to familiarize themselves to acquire skills / ability to understand everything that is heard, speaking, reading and writing in Arabic. One of proficiency is the skill to read and understand Arabic texts properly. However, in the practical realm is still encountered some problems and issues in this maharoh learning, students are still difficult to read or pronounce the word / phrase and find its meaning. This is because many students do not recognize and pronounce unfamiliar words based wazan (pronunciation rules) and sighot (type of word based dilalahnya). Of this problem researchers provide an alternative solution by presenting a pattern-based learning Arabic morphological analyzer. The objectives of this study were: 1) describe the procedures / technical-based learning Arabic morphology. 2) measure the effectiveness of pattern-based learning Arabic morphological analyzer in increasing reading competence. This study using a pre experimental design with a form of one-shot case Study. And the results of this study concluded that the pattern of learning is quite effective with indicators: 1) students are familiar and easy to pronounce and utter words corresponding wazan / shighot. 2) student easily to memory on vocabulary acquisition; origin of word and its meaning changes. 3) the students more easily and quickly understand a text with the stock of the results of the acquisition of vocabulary and understanding of the meaning of the vocabulary.Keywords: Learning Arabic, Morphology, Reading skill.